Fructose-1, 6-bisphosphate couples glycolytic flux to activation of Ras. Issue 1 (December 2017) - Peeters, Ken; Van Leemputte, Frederik; Fischer, Baptiste; Bonini, Beatriz; Quezada, Hector; Tsytlonok, Maksym; Haesen, Dorien; Vanthienen, Ward; Bernardes, Nuno; Gonzalez-Blas, Carmen; Janssens, Veerle; Tompa, Peter; et al.
Abstract Yeast and cancer cells share the unusual characteristic of favoring fermentation of sugar over respiration. We now reveal an evolutionary conserved mechanism linking fermentation to activation of Ras, a major regulator of cell proliferation in yeast and mammalian cells, and prime proto-oncogene product. A yeast mutant (tps1∆ ) with overactive influx of glucose into glycolysis and hyperaccumulation of Fru1, 6bisP, shows hyperactivation of Ras, which causes its glucose growth defect by triggering apoptosis. Fru1, 6bisP is a potent activator of Ras in permeabilized yeast cells, likely acting through Cdc25. As in yeast, glucose triggers activation of Ras and its downstream targets MEK and ERK in mammalian cells. Biolayer interferometry measurements show that physiological concentrations of Fru1, 6bisP stimulate dissociation of the pure Sos1/H-Ras complex. Thermal shift assay confirms direct binding to Sos1, the mammalian ortholog of Cdc25. Our results suggest that the Warburg effect creates a vicious cycle through Fru1, 6bisP activation of Ras, by which enhanced fermentation stimulates oncogenic potency. Yeast and cancer cells both favor sugar fermentation in aerobic conditions. Here the authors describe a conserved mechanism from yeast to mammals where the glycolysis intermediate fructose-1, 6-bisphosphate binds Cdc25/Sos1 and couples increased glycolytic flux to increased Ras proto-oncoprotein activity.